2008
DOI: 10.1161/hypertensionaha.108.112532
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin Augments Sympathetic Enhancement of the Renovascular Effects of Angiotensin II in Genetic Hypertension

Abstract: Abstract-DipeptidylIn this regard, there are 2 endogenous agonists of Y 1 Rs that would be presented to the kidney microcirculation, ie, peptide YY 1-36 (PYY ) and neuropeptide Y 1-36 (NPY 1-36 ). Both are pancreatic polypeptide-fold peptides. A fatty meal releases PYY 1-36 into the systemic circulation from endocrine L-cells in the small bowel, colon, and rectum producing physiologically active levels of PYY in plasma that are 500% to 1000% above basal circulating levels, 2-8 and this circulating PYY 1-36 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 19 publications
3
37
2
1
Order By: Relevance
“…RSNS was accomplished by placing a platinum bipolar electrode around the renal artery close to the kidney and connecting the electrode to a Grass stimulator (model SD9E; Grass Instruments, Quincy, MA) as previously described by us (35). The tissues around the electrode were kept moist with Tyrode's solution and the stimulation parameters were biphasic pulses, 1-ms pulse duration; 35 V at indicated frequencies.…”
Section: Animalsmentioning
confidence: 99%
“…RSNS was accomplished by placing a platinum bipolar electrode around the renal artery close to the kidney and connecting the electrode to a Grass stimulator (model SD9E; Grass Instruments, Quincy, MA) as previously described by us (35). The tissues around the electrode were kept moist with Tyrode's solution and the stimulation parameters were biphasic pulses, 1-ms pulse duration; 35 V at indicated frequencies.…”
Section: Animalsmentioning
confidence: 99%
“…The mechanisms underlying this interaction are unclear but might relate to altered degradation of the peptide substance P or neuropeptide Y related to DPP-4 inhibition, ultimately leading to sympathetically mediated vasoconstriction. In addition, Jackson and Mi (47) showed that in a renal perfusion model, enhancement of angiotensin-IImediated constrictor responses, owing to increases of neuropeptide Y, could be exacerbated by sitagliptin and blocked if sitagliptin were given together with a neuropeptide Y inhibitor, again suggesting enhanced vasoconstriction.…”
Section: Potential Mechanisms For the Increased Risk For Hf Associatementioning
confidence: 99%
“…Вместе с тем, ситаглиптин усиливал вазоконстриктивное действие ангиотензина II на почеч-ные сосуды в экспериментах на крысах линий Lean-ZSF1 и Obes-ZSF1 со спонтанной АГ [47]. В эксперименте на изолированной почке крыс линии SRH, предрасполо-женных к АГ, описано усиление реноваскулярного эф-фекта ангиотензина II под воздействием ситаглиптина; данный эффект был связан с ингибированием деграда-ции нейропептида Y в симпатических нервах почек [48].…”
Section: ингибиторы дпп-4unclassified